Employer Branding, Corporate Social Responsibility and Students’ Intention to Apply for the Ministry of Manpower Internship Program: The Mediating Role of Corporate Reputation - Putri Octania Utami; Febrianty Febrianty; Muhammad Irfan Pratama (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study examines students’ intention to apply for the Ministry of Manpower Internship Program by analyzing the role of employer branding, corporate social responsibility, and corporate reputation. The research was conducted among university students in Bandar Lampung because internship programs have become an important bridge between higher education and employment readiness. The main problem addressed in this study is how organizational attractiveness and social responsibility influence students’ application intention, both directly and indirectly through corporate reputation. This study used a quantitative survey design with purposive sampling. Data were collected using a structured questionnaire measured with a five-point Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares with SmartPLS 4.0. The findings show that employer branding significantly affects students’ intention to apply and corporate reputation. Corporate social responsibility also significantly affects intention to apply and corporate reputation. In addition, corporate reputation significantly affects intention to apply. The mediation results indicate that corporate reputation mediates the effect of employer branding on intention to apply, but does not mediate the effect of corporate social responsibility on intention to apply. These findings suggest that employer branding and corporate reputation are key factors in increasing students’ interest in internship programs, while CSR should be communicated more directly in relation to student development and internship benefits.